PENGARUH FAKTOR BUDAYA DAN FAKTOR SOSIAL TERHADAP KEPUTUSAN MEMBELI KERAJINAN MANIK (Studi Kasus Pada Toko Kerajinan Manik Leni Tenggarong) - Kaumbur, Olvi Marlinda (EKONOMIA, 2019)
The influence of economy and social and cultural factors of the decision of buy the craft of manic ( case study in a shop the craft of manic leni tenggarong ). Under the guidance of mr L.C.A Robin Jonathan as supervising lecturer I and Taghfirul Azhima Yoga as supervising lecturer II.The purpose of this research is to find the influence of economy and social and cultural factors of the decision of buy the craft of manic in a shop the craft of manic leni tenggarong. The theory of the research is a steady cultural factors, buy economy and social and decisions. The research was conducted in a shop the craft of manic leni tenggarong, as many as 80 samples to be taken with the methods respondents simple random sampling. Data collection to the spread of the questionnaire by using likert scale for measuring a number of indicators. The analytical technique used is multiple linear regression.The result of this research show that the economy and social and cultural factors significant together with the resolution of buy the craft of manic in a shop the craft of manic leni tenggarong. Significant cultural factors of the decision of buy the craft of manic in a shop the craft of manic leni tenggarong. Social factorsÂ  has no significant impact on the decision buy the craft of manic in a shop the craft of manic leni tenggarong